2020
DOI: 10.2147/jir.s249384
|View full text |Cite
|
Sign up to set email alerts
|

<p>“High Treg” Inflammations Promote (Most) Non-Hematologic Cancers While “Low Treg” Inflammations Promote Lymphoid Cancers</p>

Abstract: In an earlier publication, a binary classification of chronic diseases has been proposed. Chronic diseases were classified as "high Treg" or "low Treg" diseases depending on whether the pro-inflammatory or the anti-inflammatory arms of the immune response are deficient. The present work uses this model to analyze the interplay between cancer and the immune system, based on published literature. The work leans upon the etiology of alcohol and tobacco-related malignancies. The main conclusions are: triggers of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 84 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…The association between “low Treg” pathogens and autoimmune diseases was discussed in earlier publications. 8 , 9 Here we discuss the association between “low Treg” pathogens and MPNs.…”
Section: Diseases Driven By Piks Are (Mostly) Associated With “Low Trmentioning
confidence: 99%
See 4 more Smart Citations
“…The association between “low Treg” pathogens and autoimmune diseases was discussed in earlier publications. 8 , 9 Here we discuss the association between “low Treg” pathogens and MPNs.…”
Section: Diseases Driven By Piks Are (Mostly) Associated With “Low Trmentioning
confidence: 99%
“… 126 It has been shown that lymphoma starts as a “low Treg” disease, and can dwell in this state for several years, before aggressive disease develops. 9 In addition, EBV is involved in the etiology of nasopharyngeal carcinoma and gastric carcinoma. 126 Tumor-infiltrating Tregs correlate with a poor prognosis in gastric cancer but no statistically significant correlation was observed for oropharyngeal cancer.…”
Section: Pathogens That Activate Both Aiks and Piks Can Induce Both “mentioning
confidence: 99%
See 3 more Smart Citations